Diclofenac sensitizes multi-drug resistant Acinetobacter baumannii to colistin. - Fabiana Bisaro; Clay D Jackson-Litteken; Jenna C McGuffey; Anna J Hooppaw; Sophie Bodrog; Leila Jebeli; Manon Janet-Maitre; Juan C Ortiz-Marquez; Tim van Opijnen; Nichollas E Scott; Gisela Di Venanzio; Mario F Feldman (PLoS Pathogens)
Acinetobacter baumannii causes life-threatening infections that are becoming difficult to treat due to increasing rates of multi-drug resistance (MDR) among clinical isolates. This has led the World Health Organization and the CDC to categorize MDR A. baumannii as a top priority for the research and development of new antibiotics. Colistin is the last-resort antibiotic to treat carbapenem-resistant A. baumannii. Not surprisingly, reintroduction of colistin has resulted in the emergence of colistin-resistant strains. Diclofenac is a non-steroidal anti-inflammatory drug used to treat pain and inflammation associated with arthritis. In this work, we show that diclofenac sensitizes colistin-resistant A. baumannii clinical strains to colistin in vitro and in a murine model of pneumonia. Diclofenac also reduced the colistin minimal inhibitory concentration (MIC) of Klebsiella pneumoniae and Pseudomonas aeruginosa isolates. Transcriptomic and proteomic analyses revealed an upregulation of oxidative stress-related genes and downregulation of type IV pili induced by the combination treatment. Notably, the concentrations of colistin and diclofenac effective in the murine model were substantially lower than those determined in vitro, implying a stronger synergistic effect in vivo compared to in vitro. A pilA mutant strain, lacking the primary component of the type IV pili, became sensitive to colistin in the absence of diclofenac. This suggest that the downregulation of type IV pili is key for the synergistic activity of these drugs in vivo and indicates that colistin and diclofenac exert an anti-virulence effect. Together, these results suggest that diclofenac can be repurposed with colistin to treat MDR A. baumannii.